The impact of artificial intelligence on enhancing operational efficiency in Egyptian seaports - AlSaadani, Ola Abd El-Qawi; Attia, Eman F.; Soliman, Karim (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the potential of artificial intelligence (AI) to enhance operational efficiency in Egyptian seaports. Despite significant government investment in infrastructure, persistent challenges such as delays, inefficiencies, and outdated processes continue to hinder performance. The research addresses the gap in localized empirical data on AI applications in the Arab port context, with a focus on identifying the benefits, challenges, and enablers of AI adoption in Egypt’s maritime logistics sector. A mixed-methods approach was adopted, combining quantitative data from a structured survey of 510 port professionals across key Egyptian ports with qualitative insights from in-depth interviews with seven senior port managers. Quantitative data were analyzed using descriptive statistics, correlation, and regression analysis via SPSS, while qualitative data were thematically analyzed using NVivo software to enrich the interpretation of findings. The results reveal strong positive correlations between AI adoption and key performance metrics such as operational efficiency, cost reduction, process accuracy, and decision-making flexibility. Machine learning, robotics, and computer vision emerged as the most impactful technologies. However, challenges including weak digital infrastructure, limited staff training, and uneven digital readiness across ports were identified as critical barriers. Qualitative insights reinforced the quantitative findings and highlighted managerial support as crucial for successful integration. The study offers actionable recommendations for enhancing AI implementation, including investing in digital infrastructure, expanding workforce training, and fostering institutional readiness. The findings contribute localized empirical evidence to the global discourse on AI in port logistics, emphasizing the need for a tailored, inclusive digital transformation strategy in Egypt. Policymakers and port authorities can leverage these insights to drive sustainable improvements in port performance and competitiveness.